1995
DOI: 10.2105/ajph.85.5.720
|View full text |Cite
|
Sign up to set email alerts
|

Weight concerns and change in smoking behavior over two years in a working population.

Abstract: The hypothesis that weight concerns are related to less successful smoking cessation and greater relapse among ex-smokers was prospectively evaluated. A population-based sample of 4981 working women and men 17 to 71 years of age was surveyed at 32 work sites. Current and previous weight loss efforts and smoking behavior were self-reported at baseline and 2 years later. Dieting and weight concerns were unrelated to smoking cessation or relapse. However, female smokers who had previously participated in a formal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 8 publications
1
37
1
Order By: Relevance
“…13 The results of the few studies concerning the association between tobacco use and intentional weight loss in adults are somewhat contradictory probably due to methodological differences. [14][15][16][17] In a small sample of US women, Gerend dieting and weight concerns were unrelated to smoking cessation or relapse in a population-based sample of working adults. In a population-based survey in the USA, Serdula et al 16 found that current smokers were 30-40% less likely than never smokers to try to maintain their current weight compared to doing nothing to weight.…”
Section: Introductionmentioning
confidence: 96%
“…13 The results of the few studies concerning the association between tobacco use and intentional weight loss in adults are somewhat contradictory probably due to methodological differences. [14][15][16][17] In a small sample of US women, Gerend dieting and weight concerns were unrelated to smoking cessation or relapse in a population-based sample of working adults. In a population-based survey in the USA, Serdula et al 16 found that current smokers were 30-40% less likely than never smokers to try to maintain their current weight compared to doing nothing to weight.…”
Section: Introductionmentioning
confidence: 96%
“…Childhood obesity is associated with an increased risk of hyperinsulinemia, 3 insulinresistance, 4 type 2 diabetes, 5,6 hypertension, 7,8 hypercholesterolemia, 3 chronic inflammation, 9 abnormalities in endothelial function, 10 hyperandrogenemia, 4 gallstones, 11 hepatitis, 12,13 asthma, cancer 14 and orthopedic problems. 10 Obesity has also been shown to diminish children's quality of life severely 14 and is associated with decreased selfesteem 15,16 and depressive symptoms. 17 Obese children are subjected to teasing, discrimination and victimization and may be socially excluded.…”
Section: Introductionmentioning
confidence: 99%
“…4,[7][8][9][10] Weight gain from smoking cessation not only has become a barrier to quitting but also increases the risk of relapse among female smokers. [11][12][13][14][15] Although the association between smoking cessation and weight gain is well established, it is not known if the effect is through increases in body fat, muscle, or both. The relationship between smoking and body fat is complex, with crosssectional studies showing that smokers have higher waist circumference (a measure of central adiposity) than nonsmokers and also lower body mass index (BMI) [16][17][18][19][20][21] and decreased overall body fat.…”
Section: Introductionmentioning
confidence: 99%